2020
DOI: 10.1097/ico.0000000000002579
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Epidemiological Approach to Geographically Mapping Population Dry Eye Disease in the United States Through Google Trends

Abstract: Purpose: Our study fills the spatiotemporal gaps in dry eye disease (DED) epidemiology by using Google Trends as a novel epidemiological tool for geographically mapping DED in relation to environmental risk factors. Methods: We used Google Trends to extract DED-related queries estimating users' intent from 2004 to 2019 in the United States. We incorporated national climate data to generate heat maps comparing geographic, temporal, and environmental rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
14
1
Order By: Relevance
“…Environmental factors such as air pollution, wind, low humidity, use of central heating or air conditioning have been suggested to impact the integrity of the ocular surface [2,24,[40][41][42]. In the present study, air conditioning was identified as a potential risk factor for DED, but it did not show a statistically significant relationship with DED in the multivariate analysis.…”
Section: Lifestyle Exercise and Environmental Conditionscontrasting
confidence: 64%
“…Environmental factors such as air pollution, wind, low humidity, use of central heating or air conditioning have been suggested to impact the integrity of the ocular surface [2,24,[40][41][42]. In the present study, air conditioning was identified as a potential risk factor for DED, but it did not show a statistically significant relationship with DED in the multivariate analysis.…”
Section: Lifestyle Exercise and Environmental Conditionscontrasting
confidence: 64%
“…According to previously published methods, the authors included in all analyses control term data to account for fluctuations in search volume ascribed to general changes in internet traffic. 12,13 To compare the mean search volume during the COVID-19 pandemic stay-at-home period (March 1 2020, until May 31 2020) with the same time period in the prior 2 years, an unpaired t-test was performed. Multivariable regression analysis was utilized to examine the relationship between online interest for COVID-19 and interest for oculofacial plastic surgery from January 1 2020 until July 20 2020.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] The following methods were designed according to previously published methodologies. 12,13 The search query was performed with the following filters: "United States," "1/1/2004" through "7/20/2020," "All categories," "Web search." A "Health" filter was used to exclude ambiguous terms.…”
Section: Oculofacial Plastic Surgery-related Internet Searchesmentioning
confidence: 99%
“…Data sets were downloaded for symptoms and terms listed by the American Psychiatric Association for major depressive disorder: “feeling sad,” “depressed,” “depression,” “empty,” “insomnia,” “fatigue,” “guilty,” “feeling guilty,” and “suicide” [ 21 ]. To account for random variance and overall increases in search queries, data sets were also downloaded across similar time periods for control terms based on previously published studies and popular internet search terms: “sports,” “news,” “google,” “youtube,” “facebook,” and “netflix” [ 18 , 19 , 22 ]. The values of depression search intent were summed and normalized relative to the control terms for the given region and time and are represented on a scale of 0 to 100 arbitrary units (AU).…”
Section: Methodsmentioning
confidence: 99%